Impact of Nutrition on Academic Performance of Boarding Science Students in Selected Secondary Schools in Ilorin Metropolis, Kwara State, Nigeria - Bello, Zakariyau Adebayo; Obebe, Shade Felicia; Ayilara, Taibat Tayo; Sulaiman, Musa Mohammed; Abdulazeez, Bolanle Tawakalt-Anu; Ambali Rasheed, Onigbegi (Faculty of Natural and Applied Sciences Journal of Health, Sports Science and Recreation, 2024)
This study investigates the impact of nutrition on the academic performance of boarding science students in selected secondary schools within the Ilorin metropolis of Kwara State, Nigeria. With growing concerns about failing educational systems and student apathy, the research seeks to understand the role of balanced diets in enhancing academic outcomes. Adopting a descriptive cross-sectional approach, the study collected qualitative data through structured questionnaires administered to a purposively selected sample of 264 boarding students aged 13 to 17. The findings reveal that dietary practices among boarding science students often lack balance, with breakfast being frequently skipped. Such practices lead to reduced concentration, impaired cognitive abilities, and consequently, lower academic performance. Factors influencing these dietary habits encompass hunger, purchasing power, health conditions, family background, school dining menus, peer influence, and religious beliefs. These factors collectively contribute to the nutritional deficiencies observed among the students. The research underscores the importance of addressing these nutritional gaps to improve academic performance. It advocates for compulsory attendance at dining halls to promote healthy eating habits, especially during breakfast, a crucial meal for cognitive function. Furthermore, there's a pressing need for educational initiatives aimed at enlightening students on the benefits of balanced nutrition and its direct impact on academic success. In light of these findings, recommendations include the inclusion of fruits in school meals to boost nutrient intake and the implementation of orientation programs for incoming students. These programs should focus on fostering positive dietary practices from the outset of their boarding school experience. The study highlights a significant relationship between nutrition and academic performance. It emphasizes the urgency of targeted interventions to improve science students' overall well-being, enhance cognitive abilities, and ultimately, elevate scholastic achievement levels among boarding science students in Kwara State.